Introduction to stellar astrophysics - Böhm-Vitense, E. (Cambridge University Press, 1989)
This textbook introduces basic elements of fundamental astronomy and astrophysics which serve as a foundation for understanding the structure, evolution, and observed properties of stars. The first half of the book explains how stellar motions, distances, luminosities, colours, radii, masses and temperatures are measured or derived. The author then shows how data of these sorts can be arranged to classify stars through their spectra. Stellar rotation and stellar magnetic fields are introduced. Stars with peculiar spectra and pulsating stars also merit special attention. The endpoints of stellar volutions are briefly described. There is a separate chapter on the Sun and a final one on interstellar absorption. The usefulness of this text is enhanced by the inclusion of problems for students, tables of astronomical constants, and a selective bibliography.